Study on biodegradation of Miri and Masila crude oil and used car oil by microorganisms isolated from Malaysian soil and the effect of aeration and NKP addition on biodegradation process - Khairi Ali, Abulgasem Alennabi (2012)
In this study,five contaminated soil samples with benzene, used car oil and diesel were collected from five car workshops in Kuala Lumpur area,Malaysia.The microbial strains were isolated using selective media(agar containing crude oil,used car oil and benzene).Microorganisms were identified by biochemical test and then used in biodegradation experiment of two types of crude oils(Miri and Masila)and used car oil.Qualitative determination of the degradation capacity of crude oils and used car oil was driven in 24 well cell culture cluster-flat bottom,adding to each well nutrient broth medium,crude oil or used car oil and the isolated microorganism cultured in the tubes(single and mixtures)and incubated at 27-°C for 30 days.For hydrocarbons rate of biodegradation measurement,sterilized soil was distributed in petri dishes,3% w/w of two crude oils and used car oil were added,separately and then supplemented with isolated strains(single and mixtures).One Petri dish was used as a control without any microbial addition.Absorbance was determined by spectrophotometer at 360 nm and at 340 nm for crude oils and used car oil, respectively.The effect of aeration,added NPK and added microbial degraders on biodegradation of Masila crude oil and used car oil was studied. Soil was supplemented with 20% Masila crude oil and used car oil,separately.The soil was distributed into containers.Container(1)was aerated twice a week,NPK 1:1:1 was added to container(2),mixture of all isolated strains with degrading capacity was added to container(3.Finally, NPK with continued aeration in addition to the microbial mixture were applied to the last container (4). One container was used as a control without any addition (soil and contaminant only).Colony Forming Unit (CFU) of total heterotrophic microbes and hydrocarbon utilizing microbes,PH and percentage of oils degradation were determined.22 microbial strains were isolated and identified as,Achrombacter,Aeromonas,Klebsiella pneumonia, Pseudomonas,Corynebacterium,Penicillium,Enterobacteriaceae (Enteric rods),Actinobacillus,Streptomyces,budding yeast cells, Cladosporum and Geotrichum spp.The highest biodegradation result in Miri crude oil after 30 days were 54.33% and 84.61% for strain Z13 (Corynebacterium spp.)and microbial mixture of the strains isolated from Rawang and Serdang area (MS),respectively.While in Masila crude oil was 33.81% for Strain A3 (Klebsiella pneumonia) and 49.47% for microbial mixture of the strains isolated from Serdang (Smix).In used car oil biodegradation experiment,strain Z4 (Corynebacterium) had the highest degradation with 72.9%. While microbial mixture of the strains isolated from Kajang (Zmix)had 72.4 % of degradation. In the experiment of the effect of aeration,added NPK and added microbial degraders on biodegradation,the aerated container showed 56.62% of degradation after 42 days in Masila crude oil,while the container which contained NPK and was aerated and supplemented with isolated strains showed 66% degradation in used car oil.Generally,two bacterial species and one fungal species isolated were found to be effective degraders (Corynebacterium spp,Streptomyces spp.and Cladosporum spp,), respectively.The highest degradability by single strains was on used car oil which might be due to the adaptability of the isolated microbes to use it.The microbial mixtures showed higher effect on the biodegradation than the single strains.Aeration found to be the most important in the effect on the biodegradation results.